Correlations of sensory parameters with physicochemical characteristics of Argentinean honeys by multivariate statistical techniques - Patrignani, Mariela (2017)
Honey acceptability is mainly determined by its colour, crystallisation degree and aroma. In the presentwork, the sensory characteristics and physicochemical parameters of Argentinean honeys from differentecoregions were analysed. Moisture content, Pfund colour, diastase activity, hydroxymethylfurfural content,electrical conductivity, sugar profile and volatile compounds were analytically determined in honeysamples, while sensory characteristics (crystal size, fluency score, sweetness, persistence, granularity, crystallisation,colour intensity and aroma) were evaluated by a trained panel. Significant correlations werefound between honey crystallisation degree and hydroxymethylfurfural content and diastase activity(P ≤ 0.05). It could be confirmed that honey crystallisation interferes with the visual perception of colour.Floral, fresh fruit, ripe fruit, balsamic and wood aromas could be successfully linked to honey volatileprofile (P ≤ 0.05). These results demonstrate that the parameters that could best guarantee the consumers?preference can be successfully associated with the chemical composition of honey by multivariate statisticalanalysis.